(3eSCdI aj efGXQI eY GdbGVi GdHGbdGfis - (3eMeO Hf eMeO Hf GdfYeGf Hf YHO GdSdGe GdYcHQqj, CHh YHO Gddg, GdeajO, hjYQa HGHf GdeYde , J (B413 (3g`s ((3GdcGXejI s)
(3ChdgG (B:s
(3SCdfi GdbGVi GdHGbdGfi abGd CNHQhfG Yf CSdGace ai GdfU CcKjQkG Ce bdjd s
(3BNQgG (B:s
(3de jcf GdLhGH eG PcQfGg ef GdeUdMI fLRJ HMeO Gddg hGdUdGg Ydi GdfHi hBdg s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(998) s
Keywords: (3GdJhMjO hGdedd hGdfMds